A semi-reliable energy-efficient retransmission mechanism based on the sensing relevancies of source nodes for wireless image sensor networks - Daniel G. Costa (2012)
Whenever reliable transmissions are assured by retransmission mechanisms, higher packet error incur in additional energy consumption due to packet retransmissions, even though many monitoring applications can tolerate some loss in the quality of the received images. In fact, visual information retrieved from source nodes may have different relevancies for the applications, according to the desired monitoring tasks and the current sensors' poses and fields of view. We propose a semi-reliable energy-efficient hop-by-hop retransmission mechanism, where the reliability level of each packet is function of the relevance of the source nodes associated with DWT subbands. Doing so, some of the corrupted packets will not be retransmitted, saving energy of intermediate nodes with low impact to the visual monitoring quality. Â© 2012 IEEE.